2005
DOI: 10.1093/jnci/dji133
|View full text |Cite
|
Sign up to set email alerts
|

p53-Defective Tumors With a Functional Apoptosome-Mediated Pathway: A New Therapeutic Target

Abstract: Many p53-defective tumors retain activity of the apoptosome, which is therefore a potential target for cancer chemotherapy. Inhibition of ACS may be a novel strategy to induce the death of p53-defective tumor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 38 publications
3
78
0
Order By: Relevance
“…34 It was recently observed that tumor cells vary in terms of their apoptosome activity potential, and that inactivation of the apoptosome is a cause of chemoresistance and oncogenic transformation. 24,35,36 The Cell death and autophagy of Ph þ leukemias Y Kamitsuji et al expression of XIAP, and defective p53 molecules have been reported to inhibit the apoptosome. 24,37 It is believed that the natural cell death pathways are altered in apoptosomedefective cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…34 It was recently observed that tumor cells vary in terms of their apoptosome activity potential, and that inactivation of the apoptosome is a cause of chemoresistance and oncogenic transformation. 24,35,36 The Cell death and autophagy of Ph þ leukemias Y Kamitsuji et al expression of XIAP, and defective p53 molecules have been reported to inhibit the apoptosome. 24,37 It is believed that the natural cell death pathways are altered in apoptosomedefective cells.…”
Section: Discussionmentioning
confidence: 99%
“…24,35,36 The Cell death and autophagy of Ph þ leukemias Y Kamitsuji et al expression of XIAP, and defective p53 molecules have been reported to inhibit the apoptosome. 24,37 It is believed that the natural cell death pathways are altered in apoptosomedefective cells. Therefore, to overcome chemoresistance, it may be useful to develop agents that can trigger another cell death pathway, such as a caspase-independent pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The human MnSOD expression plasmid was a gift from Dr Abbadie at the Institute of Biology of Lille, France (Bernard et al, 2001). Dominant-negative mutants of human MEK1 (DN-MEK1; Wang et al, 2006) and caspase-9 (Mashima et al, 2005) were described elsewhere.…”
Section: Antibodies and Reagentsmentioning
confidence: 99%